2022
DOI: 10.1186/s12891-022-05629-7
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of midfoot and hindfoot arthrodesis with strut allograft for Müller–Weiss disease

Abstract: Background Müller–Weiss disease (MWD), a rare dysplastic disorder of the foot, is characterized by deformity, sclerosis, and fragmentation of the lateral part of navicular bone. Arthrodesis is the mainstay treatment for MWD. Generally, arthrodesis can be achieved through internal fixation with metallic implants, and morselized chip bone may be packed into the gap for better bone union. However, with this procedure, the original foot size is not maintained and support for the foot arch is not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Moreover, regression analysis revealed a positive correlation between midfoot abduction and postoperative pain after midfoot arthrodesis ( P = .007). These results are consistent with those of Harnroongroj et al 14 When reviewing previous MWD literature and scrutinizing their illustrations, we found that most researchers focused more on restoring the medial longitudinal arch, 4,10,17,19 medial column length, 10,31 hindfoot alignment, 5,18,24 and perinavicular arthrodesis through malreduction, 3,11,13,20 while overlooking midfoot abduction. The clinical AOFAS and VAS scores in the reduction group were better than those in the malreduction group (all P < .05), implying that the pain was caused not only by the degeneration of the involved joints, but also by impaired biomechanics, such as the midfoot abduction deformity represented by the TMT1dp, leading to an uneven load distribution on the foot (Figures 1, 5, and 6).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, regression analysis revealed a positive correlation between midfoot abduction and postoperative pain after midfoot arthrodesis ( P = .007). These results are consistent with those of Harnroongroj et al 14 When reviewing previous MWD literature and scrutinizing their illustrations, we found that most researchers focused more on restoring the medial longitudinal arch, 4,10,17,19 medial column length, 10,31 hindfoot alignment, 5,18,24 and perinavicular arthrodesis through malreduction, 3,11,13,20 while overlooking midfoot abduction. The clinical AOFAS and VAS scores in the reduction group were better than those in the malreduction group (all P < .05), implying that the pain was caused not only by the degeneration of the involved joints, but also by impaired biomechanics, such as the midfoot abduction deformity represented by the TMT1dp, leading to an uneven load distribution on the foot (Figures 1, 5, and 6).…”
Section: Discussionsupporting
confidence: 90%
“…Given that pathological changes in MWD mainly affect the peri-navicular joints, Fernández et al 10 proposed TNC arthrodesis in the early stage and achieved excellent consolidation results. Furthermore, surgeons have developed multiple improved surgical approaches based on midfoot arthrodesis, [2][3][4]11,13,17,20,31,32 and performed selective arthrodesis according to the range of arthritis involvement, including triple arthrodesis, TN arthrodesis, and calcaneal-cuboid arthrodesis. 19,21 Midfoot arthrodesis remains the first-line surgical intervention for treating MWD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations